Advertising and Endogenous Exit in a Differentiated Duopoly - Andrea Mantovani; Giordano Mion (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
In this paper we consider a duopoly two-stage duopoly where firms first decide whether to invest in advertising and then compete in prices. Advertising has two effects: a market enlargement for both firms and a predatory gain for the investing firm only. Both symmetric and asymmetric equilibria may arise. The two most interesting cases are a coordination game where both firms investing and non-investing are equilibria, and a chicken game where only one firm invests while the other is possibly driven (endogenously) out of the market. Our results suggest that product differentiation has an ambiguous impact on investment in advertising and that strong product substitutability may induce a coordination problem.
Keywords: 330